The Influence Of Store Atmosphere And Price On Purchasing Decisions (Survey On Consumers Of Nara Cafe Tasikmalaya) - Ulhaq, Rendi Dhya; Karmila, Mila; Wibawa, Gian Riksa (Utami Publisher, 2024)
This research was conducted with the aim of finding out the influence of store atmosphere and price on purchasing decisions for Nara Cafe Tasikmalaya. This research uses a quantitative approach using a research method, namely Associative (Causality) using data obtained directly through questionnaires distributed to 100 respondents. The technique used in this research is multiple linear regression. The research results show that: (1) Store Atmosphere and Price simultaneously have a significant effect on Purchasing Decisions: (2) Store Atmosphere partially has a significant effect on Purchasing Decisions: (3) Price partially has no significant effect on Purchasing Decisions.